Molecular epidemiology of infectious diseases - Sana Eybpoosh (Electronic Physician, 2017)
Molecular epidemiology (ME) is a branch of epidemiology developed by merging molecular biology into epidemiological studies. In this paper, the authors try to discuss the ways that molecular epidemiology studies identify infectious diseases’ causation and pathogenesis, and unravel infectious agents’ sources, reservoirs, circulation pattern, transmission pattern, transmission probability, and transmission order. They bring real-world examples of research works in each area to make each study design more understandable. They also address some research areas and study design aspects that need further attention in future. They close with some thoughts about future directions in this field and emphasize on the need for training competent molecular epidemiology specialists that are capable of dealing with rapid advances in the field.